A new genus and species of subfamily Banchinae (Hymenoptera, Ichneumonidae) from China - Sheng, Mao-Ling; Sun, Shu-Ping; Wang, Xi-Nan; Wu, Hai-Wei (Zootaxa, 2018)
A new genus, Verruca Sheng & Sun gen. nov., of the ichneumonid tribe Atrophini, subfamily Banchinae is described for one new species, Verruca dentia Sheng & Sun, sp. nov. The species was collected from Shandong and Jiangxi Provinces, situated near the northern border of the Oriental part of China. The new genus is placed within the existing key to genera. A key to the genera of Atrophini, with the apical portion of the ovipositor with ridges, is also provided.